The return of censitary suffrage? The effects of automatic voter registration and voluntary voting in Chile. Issue 3 (15th April 2016) - Contreras, Gonzalo; Joignant, Alfredo; Morales, Mauricio
Abstract : How does a change from a compulsory voting system to a voluntary one affect election turnout? It is often argued that an electoral regime under which voting is voluntary reproduces class bias or, in other words, that the rich vote more than the poor. This bias is corrected either by the introduction of compulsory voting or the existence of strong left-wing parties and trade unions able to mobilize poorer segments of the population. In this article, we put forward an alternative argument. We assert that when voting is voluntary, class bias can disappear if an election is very competitive since this affects both turnout and its socio-economic composition. To evaluate this argument, we examine the case of Chile's 2012 municipal election when voting was voluntary for the first time, instead of compulsory.